Multi-Watt high-power THz frequency quantum cascade lasers - Li, L.H; Chen, L; Freeman, J.R; Salih, M; Dean, P; Davies, A.G; Linfield, E.H (Electronics letters, 2017)
Multi-Watt high-power terahertz (THz) frequency quantum cascade lasers are demonstrated, based on a single, epitaxially grown, 24-μm-thick active region embedded into a surface-plasmon waveguide. The devices emit in pulsed mode at a frequency of ∼4.4 THz and have a maximum operating temperature of 132 K. The maximum measurable emitted powers from a single facet are ∼2.4 W at 10 K and ∼1.8 W at 77 K, with no correction being made for the optical collection efficiency of the apparatus, or absorption by the cryostat polyethylene window.